2010
DOI: 10.1158/1055-9965.epi-10-0031
|View full text |Cite
|
Sign up to set email alerts
|

International Trends in the Incidence of Testicular Cancer, 1973-2002

Abstract: Background: Whereas testicular cancer incidence rates have been widely reported in populations of Northern European ancestry, rates in other populations have been less frequently examined. In a prior report, global testicular cancer incidence rates and trends for the years 1973 to 1997 were summarized. The current report extends these analyses with an additional 5 years of data from Cancer Incidence in Five Continents.Methods: Age-standardized incidence rates over successive 5-year time periods were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
199
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(218 citation statements)
references
References 61 publications
12
199
0
7
Order By: Relevance
“…When the distribution of the patients according to stage were evaluated, it was seen that a vast majority of the patients were at an early stage and only 22.9% of them were at an advanced stage at the time of diagnosis. These findings are consistent with the findings of previous studies (Bosl et al, 1997;Dieckmann et al, 2004;Eble et al, 2004;Chia et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…When the distribution of the patients according to stage were evaluated, it was seen that a vast majority of the patients were at an early stage and only 22.9% of them were at an advanced stage at the time of diagnosis. These findings are consistent with the findings of previous studies (Bosl et al, 1997;Dieckmann et al, 2004;Eble et al, 2004;Chia et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…A study on epidemiology of TGCT showed that seminoma was the most common testicular cancer in majority of countries with tumor registries (11). Among TGCT patients, 50% were seminomatous tumors, 48% nonseminomatous tumors and 2% were spermatocytic seminomas (12).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular germ cell tumors (TGCTs) are relatively rare, representing ~1-1.5% of all malignancies diagnosed in males and ~5% of urological tumors in males in general (1). However, TGCTs are the most frequently observed solid tumor among men aged between 15 and 35 years old (2).…”
Section: Introductionmentioning
confidence: 99%